Gold(I)‐Catalyzed Reactions of 1‐(ortho‐Alkynylaryl)ureas: Highly Selective Heterocyclization and Synthesis of Mixed N, O‐Acetals. Issue 1 (8th January 2014) - Gimeno, Ana; Cuenca, Ana B.; Medio‐Simón, Mercedes; Asensio, Gregorio
Abstract Readily available 1‐(ortho‐ethynylaryl)urea derivatives undergo a selective gold/silver {[AuCl(IPr)]/AgSbF6} catalyzed N‐6‐exo‐dig or N‐5‐endo‐dig heterocyclization process in dimethylformamide (DMF) at 60 °C. Benzoxazine derivatives, i.e., the products of O‐6‐exo‐dig ring closure through the urea oxygen, could be observed under catalytic conditions only when the N‐3 basicity was substantially diminished, but were readily isolable in stoichiometric processes carried out at low temperature. The open chain amino O, O‐acetals and a series of new cyclic mixed N, O‐acetals containing the trifluoroethyl group were synthesized when the reactions were performed in ethanol or trifluoroethanol, respectively, as solvent. The procedure allows for an easy access to this versatile class of key intermediates in organic synthesis from simple starting materials. The effect of using either DMF or protic solvents on the course of the reactions is reported. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>